Integrasi Muatan Keislaman dengan Biologi di Perguruan Tinggi: Analisis Penerapan dalam Pembelajaran : Integration of Qur'anic verses with Biology science content in Higher Education: An Analysis of Its Implementation in Learning - Salsabila, Nauroh Aisy; Zulfa, Triana Atika (Program Studi Pendidikan Biologi FKIP Universitas Jambi, 2025)
The integration between Islamic teachings and biological concepts has been widely explored, but research identifying students' responses to the application of this integration in learning is still limited. This study aims to explore students' responses to the integration of biology and Quranic verses in the context of higher education. The method used is descriptive quantitative research, with data collected through questionnaires consisting of four aspects: the integration of biology with the Quran, the study of phenomena in the Quran, the use of learning resources, and the analysis of Quranic verse translations. The subjects of the study are 50 PGMI students enrolled in the Biology Science Education course (KD IPA Biologi). The results show that students have a good understanding of natural phenomena in the Quran, with the highest average score on the aspect of Phenomenon Study (2.64). However, there are challenges in linking biological material with Quranic verses, as reflected in the lowest score on the aspect of Biology Integration (2.37). This study indicates the need for more effective teaching methods to strengthen the integration between Quranic verses and biological concepts and provides insights for lecturers and educational institutions in designing relevant curricula. Thus, it is expected that students will not only gain academic knowledge but also be able to relate biological science to Islamic values more deeply Key words: integration, Quranic verses, and biological concepts, students' responses